Clinical Characteristics of COVID-19 in Active or Previously Treated Tuberculosis Patients in Turkey - Kayali, Sumeyra; Karacorlu, Fatma Nur; Yilmaz, Mustafa; Toraman, Zulal Asci; Pirincci, Edibe (Galenos Publ House, 2022)
Aim: There is limited literature on coronavirus disease-2019 (COVID-19) and tuberculosis (TB) coinfection, although high rates of coinfection between COVID-19 and other respiratory pathogens are expected. To the best of our knowledge, this is the first study to examine COVID-19 infection in patients diagnosed with active or previously treated TB in Turkey. In this study, the aim was to examine the frequency of COVID-19 and the factors affecting the frequency of COVID-19 in patients with active or previously treated TB. Methods: The population of the retrospective cohort type study consisted of patients with TB enrolled in the Elazig Tuberculosis Dispensary between January 2015 and April 2021. The TB-related data of the patients was obtained from the Public Health Management System Tuberculosis System, and the COVID-19 information was obtained from the COVID-19 Case Tracking System. The status of being alive or dead and the date of death if they were dead were obtained from the Central Population Management System. Results: 23.92% (n=105) of 439 patients with TB were COVID-19 cases. Advanced age, having at least one comorbid disease, and the presence of chronic pulmonary disease, diabetes mellitus, and heart disease increased the risk of developing COVID-19 in active or previously treated patients with TB. Conclusion: COVID-19 was detected more frequently in active or previously treated TB patients than in the general population. Within the scope of public health services implemented to prevent the spread of COVID-19 infection, priority should be given to the TB patient group and older people, especially those with comorbid chronic pulmonary disease, diabetes mellitus, and heart disease in this group.
Keywords: COVID-19; coinfection; tuberculosis; retrospective studies; diabetes mellitus